Hesperidin loaded bilosomes mitigate the nephrotoxicity induced by methotrexate; biochemical and molecular in vivo investigations - Shiemaa H. Mahmoud; Walaa A. Moselhy; Ahmed F. Azmy; Fatma I. Abo El-Ela (BMC Nephrology)
Abstract Background Drugs, chemicals, and poisons may damage kidneys and cause chronic renal disease. About 20% of community and hospital acute renal failures are drug-related. Objectives Hesperidin-loaded bilosomes (HES-BS) nanoformula was tested for nephroprotection against methotrexate (MTX)-induced kidney injury in rats. Thin-film hydration produced HES-BS nanoformula. Drug-loading capacity, encapsulation efficiency (EE %), FTIR, DSC, zeta sizer, and potential were employed for characterization, coupled with an in vitro release study. In vivo pharmacological investigations on White male albino rats measured metabolic parameters, oxidative stress indicators, Nrf2 /Keap1 and BCL2/Bax gene expression, and histopathological alterations. Results The HES-BS nanoformula was synthesized with 162 nm particles and − 21.6 mv potential charge. The Transmissions electron microscopy (TEM) showed spherical HES-BS. Hesperidin-excipient compatibility was shown by FTIR and DSC investigations on the modified formulation, with 89.1% EE%. In vitro drug release showed 56% release after eight hours and 60.1% after 24 h, with greater bioavailability than crude HES. The IC₅₀ value of hesperidin decreased from 264 µg/mL to 106.2 µg/mL upon bilosome loading in Vero cells. MTX’s nephrotoxicity was mitigated by the HES-BS nano formula’s effects on creatinine, urea, uric acid, eGFR, Na, and K levels. Malondialdehyde (MDA) and Nitric Oxide (NO) were notably decreased, whereas Glutathione (GSH) and Superoxide Dismutase (SOD) were markedly elevated. Also, Nrf2 and Bcl2 were upregulated, while Keap1 and Bax were downregulated. Additionally, the produced nanoformula improved the histopathological function. Conclusion Our novel HES-BS nanoformula had potent nephroprotective activity by reducing the toxic effects of MTX treatment by improving biochemical indicators of kidney function, oxidative stress markers, anti-apoptotic gene expression, and apoptotic gene expression, as well as histopathological improvement.